FAKTOR-FAKTOR FUNGSI FISIK KUALITAS HIDUP PENDERITA DIABETES MELITUS TIPE 2 DI KABUPATEN SLEMAN, YOGYAKARTA: ANALISIS DATA HDSS SLEMAN TAHUN 2015-2017 - Febri Indah Widhowati; Arta Farmawati; Fatwa Sari Tetra Dewi (Dian Nuswantoro Semarang, 2020)
Degenerative diseases such ac diabetes mellitus affect many aspects and the prevalence increas in the word. The aims of this study was to determine the relationship of demographic factors, lifestyle, disease complications, and therapy with physical quality of life in patients with type 2 DM (T2DM). A double cross sectional study using data from the HDSS (Demographic Health and Monitoring System) panel of the 2015-2017 Sleman wave with inclusion criteria for T2DM patients aged 25 years or more who were recruited using total sampling. The SF-12v2 questionnaire items 2a and 2b were used to measure physical function of quality of life. Univariate analysis uses t test and Z test while multivariate analysis uses logistic regression test. From this study the results of the factors of young age, which did not have hypertension complications and a history of therapy in the last 12 months had a positive effect on physical function (OR = 5.5), (OR = 5) and (OR = 2.5). It can be concluded that young age, which does not have hypertension complications, and underwent therapy in the past 12 months has a positive effect on physical function in people with T2DM.Keywords: Age, treatment compliance, hypertension complications